Leuconíquia i cultura popular - Veny, Joan (Caplletra. Revista Internacional de Filologia, 1999)
The materials from the «Atles Lingüístic del Domini Català» related to the names of «leuconíquia», or small white spots under people's nails, a geolinguistic and anthropological study is performed of the various folk names {«mentides, regals, alegries», etc.) as compared to other languages. The origin of such names is based on the belief that theyrepresent different signs (that someone has been telling lies, that there is a forthcoming present, etc.) mostly developed in the world of children.